2018
DOI: 10.1590/s1677-5538.ibju.2018.0232
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Oltipraz, nuclear factor - erythroid – 2 - related factor 2 (Nrf2), on renal damage in unilateral ureteral obstruction rat model

Abstract: Introduction: We investigated whether Oltipraz (OPZ) attenuated renal fibrosis in a unilateral ureteral obstruction (UUO) rat model. Materials and Methods: We randomly divided 32 rats into four groups, each consisting of eight animals as follows: Rats in group 1 underwent a sham operation and received no treatment. Rats in group 2 underwent a sham operation and received OPZ. Rats in group 3 underwent unilateral ureteral ligation and received no treatment. Group 4 rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…Nrf2 exerts cytoprotective and antiapoptotic effects, and is found present as an inactive complex in the cytoplasm with Keap1. In the nucleus, Nrf2 activates the expression of the HO-1 gene, which subsequently alleviates oxidative stress-induced cellular damage ( 8 , 14 ). In addition, HO-1 is a phase II detoxifying enzyme and an anti-inflammatory reactive protein ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 exerts cytoprotective and antiapoptotic effects, and is found present as an inactive complex in the cytoplasm with Keap1. In the nucleus, Nrf2 activates the expression of the HO-1 gene, which subsequently alleviates oxidative stress-induced cellular damage ( 8 , 14 ). In addition, HO-1 is a phase II detoxifying enzyme and an anti-inflammatory reactive protein ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the severity of CP-induced nephrotoxicity is related to the activation of NF-κB, and conversely, the inflammatory response and severity of nephrotoxicity can be attenuated through the inhibition of NF-κB activity ( 12 , 13 ). In addition, numerous studies have suggested a role for nuclear factor E2-related factor 2 (Nrf2) in the regulation of physiological processes that serve to inhibit the development and progression of CP-induced renal damage ( 14 , 15 ). It has been reported that the absence of Nrf2 exacerbates CP-induced nephrotoxicity, whilst the pharmacological activation of Nrf2 has been observed to inhibit CP-mediated nephrotoxicity ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oltipraz, 5-(2-pyrazinyl)-4-methyl-1,2-dithiole-3-thione is an inducer of Nrf2 that has exhibited antioxidant, anticancer, and regenerative properties in different animal models and clinical trials by inducing the NQO1 isoenzyme [33,34,35,36]. Treatment with oltipraz also prevents insulin resistance and obesity associated with type 2 diabetes [37], and attenuates heart failure [38], renal and liver fibrosis [39,40], and kidney injury [41]. The effects of oltipraz on the nociceptive responses and depressive-like behaviors that accompany chronic pain and on microglial activation and subsequent induced pain signaling pathways in the spinal and supraspinal regions of sciatic nerve-injured animals have not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…A phase 2a study showed that 24-week oltipraz treatment significantly reduced the liver fat content in patients with NAFLD (PMK-N01GI1) [ 56 ] ( Table 1 ). Oltipraz ameliorated renal fibrosis in a unilateral ureteral obstruction rat model [ 57 ]. However, human studies for diabetic nephropathy or CKD are not planned.…”
Section: Common Drug Pipelines For Nafld/nash and Diabetic Nephropmentioning
confidence: 99%